The Influence of Work Facilities, Communication and Motivation on Employee Performance at the Pioneer Air Transport Subsidy Service Elelim Coordinator - Bless, Genos Imanuel; Christian, Ferdinandus; Astini, Rina (Maneggio, 2025)
This research was conducted on employees at the Regional Coordinator of Pioneer Air Transport Subsidy Services. The purpose of this study was to determine and analyze the influence of work facilities, Communication and Motivation on employee performance, both partially and simultaneously. This research is a quantitative study using Multiple Regression using SPSS Version 27 software. The population in this study were all employees at the Regional Coordinator of Pioneer Air Transport Subsidy Services serving 16 pioneer routes. A total of 80 respondents and samples were taken from the entire population. The results of the study indicate that partially work facilities have a significant effect on employee performance, Communication does not have a significant effect on employee performance, motivation has a significant effect on employee performance and simultaneously work facilities, Communication and motivation have a significant effect on employee performance at the Regional Coordinator of Pioneer Air Transport Subsidy Services.